Lucky [large type] - Smiley, Jane (Random House Large Print, 2024)
"Before Jodie Rattler became a star, she was a girl growing up in St. Louis. One day in 1955, when she was just six years old, her Uncle Drew took her to the racetrack, where she got lucky - and that roll of two-dollar bills she won has never since left her side. Jodie thrived in the warmth of her extended family, and then - through a combination of hard work and serendipity - started a singing career, which catapulted her from St. Louis to New York City, from the English countryside to the tropical beaches of St. Thomas, from Cleveland to Los Angeles, and back again. Jodie comes of age in recording studios, backstage, and on tour, and tries to hold her own in the wake of Janis Joplin, Joan Baez, Judy Collins, and Joni Mitchell. Yet it feels like something is missing. Could it be true love? Or is that not actually what Jodie is looking for? Full of atmosphere, shot through with longing and exuberance, romance and rock'n'roll, Lucky is a story of chance and grit and the glitter of real talent, a colorful portrait of one woman's journey in search of herself"--